2019
DOI: 10.1016/j.ijpx.2019.100016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of poloxamer in situ forming gels for bedaquiline fumarate salt and pharmacokinetics following intramuscular injection in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…The dissolution profile of the empty formulation is shown in Figure 9 . As previously confirmed by other authors, the dissolution of the hydrogel occurs constantly and rapidly, that is, virtually 100% after 24 h [ 48 ]. This result is probably due to the high solubility of P407 in aqueous media and this is important for the design of an in situ gelling formulation because the dissolution properties modulate the drug leakage at the administration site [ 83 ].…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The dissolution profile of the empty formulation is shown in Figure 9 . As previously confirmed by other authors, the dissolution of the hydrogel occurs constantly and rapidly, that is, virtually 100% after 24 h [ 48 ]. This result is probably due to the high solubility of P407 in aqueous media and this is important for the design of an in situ gelling formulation because the dissolution properties modulate the drug leakage at the administration site [ 83 ].…”
Section: Resultssupporting
confidence: 76%
“…Thanks to their versatility, these formulations could be employed for various biomedical applications and administration routes (e.g., subcutaneous or intramuscular) [45,48,84,86]. For examples, previous studies demonstrated that rutin significantly increases the fibroblast proliferation and the collagen production, being a support in wound-healing therapy [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, poloxamer 407 gels offer weak mechanical strength for applications under shear [ 60 ] as a result of the shear thinning character, [ 104 ] rapid dissolution, [ 105 ] and weak mucoadhesion. [ 106 ] Consequently, poloxamer 407 gels display poor residence times in vivo, with one study estimating that ≈60% of a poloxamer gel was removed from the vagina of mice after 1 h. [ 107,108 ] Additionally, minor dilution may elevate T gel above body temperature and reverse gelation, as seen in vivo after ocular administration. [ 18 ] There is a need for novel thermoreversible gelators, but crucially these materials must offer clear advantages over poloxamer 407 where the expense of translating technologies is substantial and risk of failure must be mitigated during material development.…”
Section: Thermoreversible Gelatorsmentioning
confidence: 99%
“…From the results of the study obtained results that there was an increase of each polymer, stable does not show any meaningful changes, and there is a continuous release of the drug for 6 hours, to treat periodontal. In situ formulations of poloxamer gel 388 and poloxamer 407 for intramuscular injection use showed results that poloxamer in situ formed the gel for about 6 hours as well as having a continuous release of the drug in the short term observed in mice for up to 24 hours (Hemelryck et al, 2019).…”
Section: Poloxamer (Pm) Combination Gel Forming Agent Formulationmentioning
confidence: 99%